Growing up (being) without a mother: children's experiences during maternal imprisonment - Luciana de Lione Melo; Circéa Amália Ribeiro (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to understand, through dramatic therapeutic play, children's experiences during maternal imprisonment. Methods: this is a phenomenological study in the light of Winnicott's theoretical framework carried out in a philanthropic assistance center in the capital of São Paulo, with eight children aged three to ten who participated in an interview mediated by dramatic therapeutic play session. Results: two categories emerged: Children being without a mother: a storm with lightning and thunder and Children growing up without a mother: drizzle, heavy rain and some rays of sun. Final considerations: children revealed that, even in the absence of their mothers, it is possible to continue being and growing. Therapeutic play allowed children to give voice to their experiences, surrounded by concerns and limitations, in addition to unveiling an unknown social context.